The articulated stinger optimization design - Pornpat Samutchaikit; Chiu, Gregory L.F.; Pornpong Asavadorndeja; Pennung Warnitchai; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
This thesis presents the articulated stinger optimization design. The goal of the study is to develop the suitable optimal stinger model in South-East Asia region under verifying the recommended practice. The two objectives are to perform the stinger optimization in terms of stinger structural design and evaluations of stinger performance under regulation and standard code design and to develop the stinger model to be primary concept selection of stinger design in SE-Asia region. Besides the additional feature which is extended from single stinger design, this study proposes the considerations of the stinger structural arrangement and stinger design variation through the stinger structural configurations. The stinger optimization with the scoring approach is applied to find out the suitable stinger structure for the stinger weight requirement. The stinger cross-section configurations and stinger aspect ratio are t~ stinger structural arrangement which is developed to design the stinger model. Additionally, the stinger design variations consisting of the length of stinger, the diameter of tubular and material grade are considered into the stinger structural arrangements in terms of pipelay performance evaluation and stinger stability evaluation. All of the stinger structural configurations are implemented in the stinger optimization by scoring and plotted to be the stinger concept selections. The solutions of the stinger structural configurations present that the stinger structure of type 1 comes up with the maximum of the net buoyancy and weight ratio. For the pipelay performance evaluation, only the increasing of the stinger length has an effect with stinger performance directly from the fixed tension on pipeline to catenary's profile. As the stinger stability is evaluated, the stinger structure of type 5 comes up with the maximum of the tilting angle. Finally, the stinger optimization chart selections are utilized to be a general guidance of stinger design for stinger configurations with specified stinger length.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Offshore Technology and Management, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Underwater pipelines